Correlation between skin temperature in the lower limbs and biochemical marker, performance data, and clinical recovery scales. - Gabriela de Carvalho; Carlos Eduardo Girasol; Luiz Guilherme Cruz Gonçalves; Elaine Caldeira Oliveira Guirro; Rinaldo Roberto de Jesus Guirro (PLoS ONE)
The aim of this study was to evaluate the correlation between tools commonly used in the detection of physiological changes, such as clinical complaints, a biochemical marker of muscle injury, and performance data during official matches, with infrared thermography, which has been commonly used in the possible tracking of musculoskeletal injuries in athletes. Twenty-two athletes from a professional soccer club (age 27.7 ± 3.93 years; BMI 24.35 ± 1.80 kg/cm2) were followed during the season of a national championship, totaling 19 matches with an interval of 7 days between matches. At each match, the athletes used a Global Positioning System (GPS) device to collect performance data. Forty-eight hours after each match, every athlete's perception of recovery, fatigue, and pain was documented. Blood was collected for creatine kinase (CK) analysis, and infrared thermography was applied. Only athletes who presented pain above 4 in either limb were included for thermographic analysis. Each thermographic image was divided into 14 regions of interest. For statistical analysis, we included only the images that showed differences ≥ 1° C. Data normality was verified by the Kolmogorov-Smirnov test with Dallal-Wilkinson-Lilliefors correction. We used the Pearson correlation coefficient to verify the correlation between infrared thermography and the biochemical marker, performance data, and clinical recovery scales. No correlation was observed between mean skin temperature and blood CK levels, pain level, perception of recovery, and fatigue perception (r <0.2, p>0.05). Thus, infrared thermography did not correlate with CK level, pain, fatigue perception, or recovery, nor with performance variables within the field.